Development History And Prospects Of Eco-Cities - Allaberganov H.F. (Zien Journals, 2025)
In the article, the history of the emergence of Eco-cities, the founder, terms and theories, main strategies and solutions, development prospects, as well as information on existing eco-cities in the world are presented
Keywords: ecocity; infrastructure; landscape; green ecocity